Distributing a metabolic pathway among a microbial consortium enhances production of natural products - Zhou, Kang (Nat Biotechnol, 2015)
Metabolic engineering of microorganisms such as Escherichia coli and Saccharomyces cerevisiae to produce high-value natural metabolites is often done through functional reconstitution of long metabolic pathways. Problems arise when parts of pathways require specialized environments or compartments for optimal function. Here we solve this problem through co-culture of engineered organisms, each of which contains the part of the pathway that it is best suited to hosting. In one example, we divided the synthetic pathway for the acetylated diol paclitaxel precursor into two modules, expressed in either S. cerevisiae or E. coli, neither of which can produce the paclitaxel precursor on their own. Stable co-culture in the same bioreactor was achieved by designing a mutualistic relationship between the two species in which a metabolic intermediate produced by E. coli was used and functionalized by yeast. This synthetic consortium produced 33 mg/L oxygenated taxanes, including a monoacetylated dioxygenated taxane. The same method was also used to produce tanshinone precursors and functionalized sesquiterpenes.